Reverse Trigger in Ventilated Non-ARDS Patients: A Phenomenon Can Not Be Ignored! - Lin, Zhimin; Zhou, Jing; Lin, Xiaoling; Wang, Yingzhi; Zheng, Haichong; Huang, Weixiang; Liu, Xiaoqing; Li, Yimin; Zhong, Nanshan; Huang, Yongbo; Xu, Yuanda; Sang, Ling (Frontiers in Physiology, 2021)
Background and Aims: Reverse triggering (RT) is a form of dyssynchrony reported in patients with acute respiratory distress syndrome (ARDS). The role of RT in ventilated patients without ARDS remains unclear. Here, we investigated the incidence, characteristics, and physiologic consequences of RT in ventilated patients without ARDS. Methods: A retrospective study involved six ventilated patients without ARDS. An esophageal balloon catheter was placed for measurement of respiratory mechanics. An esophageal balloon catheter was placed for measurement of respiratory mechanics. The occurrence of RT, duration of entrainment, entrainment pattern or ratio, phase delay (dP) and phase angle (θ), RT phenotypes, effects of RT, and clinical correlations of RT were analyzed. Results: RT was detected in four (66.7%) patients, and the occurrence of RT varied from 19.0% to 88.6% of the recording time in these four patients. One patient showed a stable 1:1 ratio, and mid-cycle RT was the most common phenotype. However, the remaining patients showed a mixed ratio, and late RT was the most common phenotype, followed by RT with breath stacking. The median (interquartile range) dP and θ were 0.39 (0.32–0.98) seconds and 60.52º (49.66º–102.24º), respectively. The median dP and θ were shorter in early RT with early and delayed relaxation and longer in mid and late RT and RT with breath stacking. The muscle pressure varied among patients and phenotypes, and higher muscle pressure was generated in early RT, delayed relaxation, and mid-cycle RT. When RT occurred, the esophageal pressure (Peso) increased by 17.27 (4.91–19.71) cmH2O compared with controlled breathing, and the average incremental change in Peso showed wide interpatient and intrapatient variability. A larger change in Peso was always generated in early RT with delayed relaxation and in mid-cycle RT, accompanied by a significant increase in transpulmonary pressure of 9.12 ± 0.75 and 16.10 ± 6.23 cmH2O, respectively. Conclusions: RT can occur in ventilated patients without ARDS. The RT pattern and phenotype in these patients are similar to those in patients with ARDS. Additionally, RT appears to alter lung stress and delivered volumes.